LEGAL AND FINANCIAL REGULATION OF AI IN SERBIA, LATVIA, AND THE EU - Dejanović, Mirjana (Serbian political thought, 2025)
Artificial Intelligence (AI) is being rapidly integrated across numerous sectors, with the financial industry at the forefront of technological transformation. It is influencing processes such as credit evaluation, fraud detection, risk modelling, and personalised financial services. This expansion increases the need for coherent legal frameworks, ethical governance, and financial sustainability, particularly regarding user protection, algorithmic transparency, safety, and liability for negative outcomes. This study offers a comprehensive comparative analysis of AI regulatory frameworks in the Republic of Serbia, Latvia, and the European Union (EU). Using a multidisciplinary qualitative methodology that integrates normative legal analysis, economic evaluation, and ethical considerations, the research is investigates Serbia’s harmonisation efforts with EU standards, Latvia’s implementation of the EU AI Act and complementary financial mechanisms, and the EU’s comprehensive regulatory architecture, including the AI Act and GDPR. Key findings identify shared legal challenges such as accountability, transparency, data protection, and the agility of regulatory frameworks in adapting to rapid AI innovation. From a financial perspective, the study identifies compliance costs for small and medium-sized enterprises (SMEs), confusion in liability distribution, and budgetary pressures on supervisory authorities. Regulatory fragmentation presents a significant barrier to cross-border AI innovation and internal market coherence. The paper concludes with policy recommendations focused on enhancing regulatory harmonisation, financial feasibility, and ethical guidance, aiming to foster sustainable AI integration that balances innovation with social protections.
Keywords: Artificial Intelligence; legal regulation; financial regulation; ethics; Serbia; Latvia; European Union